The Use of Cooperative Learning Strategies to Enhance the Students Motivation in Speaking English - Atika, Meilani Fara; Imaniar, Fahmy; Khasanah, Uswatun (ICONELT, 2024)
This study was conducted to explore the use of cooperative learning in enhancing students' motivation to speak English at SMP Negeri 22 Surabaya. The research approach is qualitative with a case study design which involves semi-structured interviews with three grade VIII students and an open-ended questionnaire to 32 students. The results showed that cooperative learning can enhance students' motivation in speaking in various aspects. The students reported improvements in confidence, interest, goal achievement, and fulfillment of students' needs. In addition, the study also highlighted the favorable influence of family, school and community environment on students' motivation to learn with cooperative learning. Although cooperative learning shows positive responses, it requires diverse activities, relevant materials, and ample opportunities for practice. Teachers are encouraged to create a supportive and engaging learning environment with cooperative learning to foster students' motivation in enhancing English speaking skills.